The Business Aspect of Innovative Environment of Regions on the Basis of Modernization the Investment Policy - SMAILOVA, Zhanara; ABDULLINA, Gulnar; UASHOV, Gilash; SEITBATKALOVA, Aliya; VIKULENKO, Julia (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The article presents some results of the analysis of entrepreneurial activity in the regions of Kazakhstan. The author focuses on the formation of regional innovation infrastructure, the increasing role of developing and improving mechanisms of interaction between authorities and business. The role of state regulation of innovation processes at the regional level. The specific results from the use of different tools supporting innovative entrepreneurship in the region.